Analisis Kompetensi Petani Pepaya California (Studi Kasus Kelompok Tani Merta Giri Kusuma Desa Abang, Kecamatan Abang, Kabupaten Karangasem) - I GEDE ARTHA SUDIARSANA; DWI PUTRA DARMAWAN; I DEWA GEDE RAKA SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Competence Analysis of California Papaya Farmers (A Case Study of MertaGiri Kusuma Farmer Group of Abang Village, Abang Sub-District ofKarangasem Regency) The Ministry of Agriculture in the Strategic Plan 2015-2019 has a Gross DomesticProduct target of 3.80% growth in the agricultural sector. Increased farm productivityis realized in the optimal utilization of land potential by applying the concept ofagribusiness maximally. Efforts to increase productivity are conducted by increasingthe competence of farmers namely knowledge, technical and managerial competence.The purpose of the study is to determine the level of competence of farmers, the levelof productivity of California papaya farming, and the relationship betweencompetence with productivity of California papaya farming. The research wasconducted at Merta Giri Kusuma Farmer Group, Abang Village, Abang Sub-District,Karangasem Regency for 5 months. There are 20 members as population or therespondents taken by the census technique. Data analysis method used qualitativedescriptive analysis and Rank Spearman correlation statistical analysis. In general,the competence of farmers is very significant ly related to the productivity ofCalifornia papaya farming. A very real relationship at the 0.01 level is technicalcompetence with a correlation coefficient of 0.835 and managerial competence witha correlation coefficient of 0,599. While the competence that is significantly relatedto the productivity of farming at the 0.05 level is the knowledge competence with thecorrelation coefficient of 0.465.